Are synthetic peptides real toxic allergens? a comprehensive literature review and update on therapeutic and adverse toxic immunogenic potentials of peptides -truth or dare - Y. Issa, Sahar; Carmichael, R. (International Journal of Pharmacology and Toxicology, 2020)
In the pharmaceutical industry, there is much debate about how to translate current guidelines on biotherapeutic immunogenicity testing into a real-life strategy that meets the regulatory requirements of newly discovered pharmaceutical peptides. This paper will present a consensus view on the essential elements for biotherapeutic immunogenicity consideration for pharmaceutical synthetic peptides to ensure patient safety and allow successful market entry. This paper's scope is limited to aspects relevant to the biotherapeutic synthetic peptide pharmaceuticals and does not include necessary academic immunogenicity studies. Medical research shows little support for antigenic or allergic reactions to short synthetic peptides. These negligible results warranted a detailed literature review to examine antigens and allergens linked to peptides.Â